Quality of Life in Hypertensive Teachers of regular basic education who go to an Establishment during the health Emergency due to COVID-19 in North Lima - Asencios-Trujillo, Lucia; Asencios-Trujillo, Lida; La Rosa-Longobardi, Carlos; Gallegos-Espinoza, Djamila; Piñas-Rivera, Livia (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The quality of life in hypertensive teachers of regular basic education is one of the priorities committed to health well-being, since it will depend on how the person can minimize the risks due to this disease, so the research objective is to determine the quality of life in hypertensive teachers of regular basic education who come to an establishment during the health emergency due to COVID-19 in North Lima. It is a quantitative, descriptive-transverse study, consisting of a population of 131 hypertensive teachers of regular basic education who answered a questionnaire on sociodemographic aspects and the questionnaire on quality of life in hypertension. In their results we can observe that 64,1 % (n=84) of hypertensive teachers of regular basic education have a good quality of life, 9,2 % (n=12) regular quality of life and 26,7 % (n=35) poor quality of life. In conclusion, strategies should be made to promote and prevent hypertension, and thus allow the population the necessary information about the disease and how to counteract it.